(untitled) (Proceedings of the International Conference on Education, 2021)
Internet technology has transformed traditional commerce, resulting in entrepreneurship becoming digital entrepreneurship. Consequently, a learning process that encourages learners to enhance their digital entrepreneurship is essential for the 21st Century. This research aims to study academic achievement by utilizing the collaborative experiential learning model using the digital marketplace and comparing academic achievement. The research approach is divided into 2 phases: a study of academic achievement utilizing the collaborative experiential learning model using the digital marketplace and compare academic achievement with more traditional learning approaches. The sample groups consisted of three groups. The participants were selected using random cluster sampling. Data collection was done using pretest-posttest and the standard deviation (S.D.), t-test, and one-way analysis of covariance (ANCOVA) of the data were used for statistical analysis. The research results found that: the academic performance of the learner group utilizing the collaborative experiential learning model using the digital marketplace was higher than that of the learner groups using the collaborative experiential learning process and the traditional instruction method. In addition, each of the groups considered exhibit a different academic achievement. The fact that there is higher academic achievement utilizing the collaborative experiential learning model using the digital marketplace shows that instructors can use this model for instruction purposes.